2007
DOI: 10.1359/jbmr.070607
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Ranelate Treatment Improves Trabecular and Cortical Intrinsic Bone Tissue Quality, a Determinant of Bone Strength

Abstract: Beside its influence on determinants of bone strength (geometry, microarchitecture), which is likely to be related to a cellular effect, strontium ranelate improves bone tissue quality as evaluated by nanoindentation, increasing elastic modulus, hardness, and dissipated energy in vertebrae of rats treated for 104 wk with daily dose from 0 to 900 mg/kg. Introduction:We previously showed that strontium ranelate treatment improves the mechanical properties of the vertebral body and long bone midshaft in intact ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
116
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(131 citation statements)
references
References 29 publications
11
116
2
2
Order By: Relevance
“…Another factor that strongly affects bone strength is the quality of bone matrix (Ammann et al 2007). Glp1r KO mice presented with a decrease in maximum load (K17%), hardness (K19%), and dissipated energy (K15%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor that strongly affects bone strength is the quality of bone matrix (Ammann et al 2007). Glp1r KO mice presented with a decrease in maximum load (K17%), hardness (K19%), and dissipated energy (K15%).…”
Section: Discussionmentioning
confidence: 99%
“…Before mechanical testing, the femurs were thawed overnight and rehydrated in saline for 24 h at room temperature as described elsewhere (Ammann et al 2007). Three-point bending strength was measured with a constant span length of 10 mm.…”
Section: Bone Mechanical Testingmentioning
confidence: 99%
“…In mice, this is reflected in an increase in vertebral bone mass. Studies in rats have demonstrated that in addition to the increase in bone mass, there is an increase in cortical thickness and an improvement in trabecular and cortical microarchitecture, leading to an increased bone quality and strength [Ammann et al 2004[Ammann et al , 2007. In ovariectomized rats, an established animal model for postmenopausal osteoporosis, strontium ranelate was able to prevent bone loss by decreasing bone resorption while maintaining bone formation not only in the short term [Marie et al 1993], but also in the long term [Bain et al 2009].…”
Section: Determinants At the Tissue Level: In Vivo Evidencementioning
confidence: 99%
“…Considering the poor quality and quantity of bone in osteoporosis, there are efforts to enhance fracture healing in this situation. [9][10][11] In treatment of osteoporosis, vitamin D3 (vitD3) and calcium supplementation has been considered a baseline therapy. It has been shown that administration of antiresorptive agents sustains or increases bone mass by suppressing bone resorption while maintaining normal bone formation.…”
mentioning
confidence: 99%